The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00411-012-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced side effects by proton microchannel radiotherapy: study in a human skin model

Abstract: The application of a microchannel proton irradiation was compared to homogeneous irradiation in a three-dimensional human skin model. The goal is to minimize the risk of normal tissue damage by microchannel irradiation, while preserving local tumor control through a homogeneous irradiation of the tumor that is achieved because of beam widening with increasing track length. 20 MeV protons were administered to the skin models in 10- or 50-μm-wide irradiation channels on a quadratic raster with distances of 500 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
126
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(137 citation statements)
references
References 40 publications
1
126
0
2
Order By: Relevance
“…As in the previous study (Zlobinskaya et al 2013), the reconstructed human skin model (EFT400; EpiDermFT TM , surface area 1 cm 2 ) was obtained from MatTek Corporation, Ashland, MA, USA. This three-dimensional, multilayered, differentiated tissue model with an epidermal and a dermal layer consists of human-derived epidermal keratinocytes and dermal fibroblasts, cultured on special cell culture inserts.…”
Section: Tissue Constructmentioning
confidence: 99%
See 4 more Smart Citations
“…As in the previous study (Zlobinskaya et al 2013), the reconstructed human skin model (EFT400; EpiDermFT TM , surface area 1 cm 2 ) was obtained from MatTek Corporation, Ashland, MA, USA. This three-dimensional, multilayered, differentiated tissue model with an epidermal and a dermal layer consists of human-derived epidermal keratinocytes and dermal fibroblasts, cultured on special cell culture inserts.…”
Section: Tissue Constructmentioning
confidence: 99%
“…First experimental evidence has demonstrated that a proton microchannel irradiation reduces irradiation effects in a human skin model in comparison with conventional broad-beam irradiation (Zlobinskaya et al 2013). In this study, 20-MeV protons were applied on the central 4 9 4 mm 2 of the skin in a focused microchannel mode (50-lm-wide channels on a 500 9 500 lm 2 matrix) or a homogeneous mode with the same mean dose of 2 Gy at the ion microprobe SNAKE in Munich (Superconducting Nanoprobe for Applied nuclear [Kern] physics Experiments; Hauptner et al 2004;Greubel et al 2008;Schmid et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations